Mass proxy quality of massive halo properties in the illustrisTNG and flamingo simulations: I. Hot gas - Aljamal, Eddie; Evrard, August E; Farahi, Arya; Pillepich, Annalisa; Nelson, Dylan; Schaye, Joop; Schaller, Matthieu; Braspenning, Joey (Monthly notices of the Royal Astronomical Society, 2025)
We examine scale and redshift dependence of mass-property relations (MPRs) for five hot gas properties of two large group- bservationsand cluster-scale halo samples realized by the Illustris tng, TNG-Cluster, and FLAMINGO cosmological hydrodynamical simulations. For intrinsic properties of (i) hot gas mass (Mgas), (ii) spectroscopic-like temperature (Tsl), (iii) soft-band X-ray luminosity (LX), and (iv) X-ray (YX), and (v) Sunyaev-Zel’dovich (YSZ) thermal energies, we use MPR parameters to infer mass proxy quality (MPQ) - the implied scatter in total halo mass conditioned on a property - for haloes with M500 ≥ 10 13 M}_\odot$ at redshifts, \in \lbrace 0, 0.5, 1, 2\rbrace$. We find: (1) in general, scaling relation slopes and covariance display moderate to strong dependence on halo mass, with redshift dependence secondary; (2) for haloes with $M_{\rm 500c}> 10^{14}\, {\rm M}_\odot$, scalings of $M_{\rm gas}$ and $Y_{\rm SZ}$ simplify toward self-similar slope and constant intrinsic scatter (5 and 10 per cent, respectively) nearly independent of scale, making both measures ideal for cluster finding and characterization to $z=2$; (3) halo mass-conditioned likelihoods of hot gas mass and thermal energy closely follow a lognormal form; and (4) despite normalization differences up to 0.4 dex between the two simulations, higher order scaling features such as slopes and property covariance show much better agreement. Slopes show appreciable redshift dependence at the group scale, while redshift dependence of the scatter is exhibited by low-mass flamingo haloes only; (5) property correlations are largely consistent between the simulations, with values that mainly agree with existing empirical measurements. We close with a literature survey placing our MPR slopes and intrinsic scatter estimates into community context.
Veröffentlicht: 01. Oktober 2025
Gesehen am 10.12.2025